Design and fabrication of robust, rapid self-healable, superamphiphobic coatings by a liquid-repellent "glue + particles" approach. (5th December 2017) - Zhang, Hao; Tan, Jiaojun; Liu, Yibin; Hou, Chunping; Ma, Yong; Gu, Junwei; Zhang, Baoliang; Zhang, Hepeng; Zhang, Qiuyu
Abstract: The "glue + particles" approach has presented an excellent idea for promoting the practicability of superamiphiphobic surfaces. However, strong polar materials, such as epoxy and polyurethane, are usually employed as adhesives. The superamphiphobic behavior will be immediately lost when parts of superhydrophobic particles are removed. Thus, a glue with robust self-healing liquid-repellence is desirable, but remains challenging to realize. Herein, a robust, self-healable, superamphiphobic film was fabricated by a liquid-repellent "glue + particles" approach. The coating based on a sol-gel network showed exceptional liquid-repellency to low surface tension liquids including ethanol. The designed coating is based on robust sol-gel network dangling fluoroalkyl chains which integrates the bonding and self-healing mechanisms for providing a longer usage life. It could withstand at least 400 cycles of abrasion under severe stress (45 kPa), strong acid/base solution, hot-liquids and smudge treatment without apparently changing the superamphiphobicity. This novel and effective coating system may be useful for the development of robust protective clothing for various applications. Graphical abstract: Highlights: An intriguing liquid-repellent "glue + particles" approach has been presented. The coating based on a sol-gel silica network shows exceptional liquid-repellency. The coating can restore the super liquid-repellent properties to multi-damages. The sol-gel network integrates two mechanisms for a long-lived superamphiphobic coating.